Chemotherapy and the somatic mutation burden of sperm - Picciotto, Shany; Arenas-Gallo, Camilo; Toren, Amos; Mehrian-Shai, Ruty; Daly, Bryan; Rhodes, Stephen; Prunty, Megan; Liu, Ruolin; Bohorquez, Anyull; Grońska-Pęski, Marta; Melanaphy, Shana; Callum, Pamela; et al. (JCI insight, 2025)
Many chemotherapeutic agents impair cancer growth by inducing DNA damage. The impact of these agents on mutagenesis in normal cells, including sperm, is largely unknown. Here, we applied high-fidelity duplex sequencing to 94 samples from 36 individuals exposed to diverse chemotherapies and 32 controls. We found that in many of the sperm samples from men exposed to chemotherapy, the mutation burden was elevated as compared with controls and the expected burden based on trio studies, with 1 patient having a more than 10-fold increase over that expected for age. Saliva from this same individual also had a markedly higher mutation burden. We then validated this finding using other tissues, also finding an increased mutation burden in the blood and liver of many patients exposed to chemotherapy as compared with unexposed controls. Similarly, mice treated with 3 cycles of cisplatin had an increased mutation burden in sperm but also in the liver and hematopoietic progenitor cells. These results suggest an association between cancer therapies and mutation burden, with implications for counseling patients with cancer considering banking sperm before therapy and for cancer survivors considering the trade-offs of using banked sperm as compared with conceiving naturally.